2006
DOI: 10.1624/105812406x92949
|View full text |Cite
|
Sign up to set email alerts
|

Doula Support and Attitudes of Intrapartum Nurses: A Qualitative Study from the Patient's Perspective

Abstract: Although the roles of the intrapartum nurse and professional doula differ markedly, they serve women best if their roles complement each other. For doulas and nurses to work well together in order to facilitate a positive birth experience for the patient, they would logically need to develop a relationship based on mutual respect. The purpose of this pilot qualitative study was to examine the level of acceptance shown by intrapartum nurses for doula support, as perceived by the parturient woman. Implications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 19 publications
0
36
0
6
Order By: Relevance
“…Lantz et al (2005) suggested that some interprofessional confl ict would be expected as doulas evolve as a new maternity care discipline. Many authors have suggested that tension between practitioners and doulas is likely because of overlap in roles (Ballen & Fulcher, 2006;Gilliland, 1998;Lantz et al, 2005;Stevens et al, 2011) or when some doulas work outside their scope of practice by giving medical advice (Ballen & Fulcher, 2006;Gilliland, 1998Gilliland, , 2002Papagni & Buckner, 2006;Stevens et al, 2011). In rare cases, doulas have been asked to leave the labor room (Eftekhary et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lantz et al (2005) suggested that some interprofessional confl ict would be expected as doulas evolve as a new maternity care discipline. Many authors have suggested that tension between practitioners and doulas is likely because of overlap in roles (Ballen & Fulcher, 2006;Gilliland, 1998;Lantz et al, 2005;Stevens et al, 2011) or when some doulas work outside their scope of practice by giving medical advice (Ballen & Fulcher, 2006;Gilliland, 1998Gilliland, , 2002Papagni & Buckner, 2006;Stevens et al, 2011). In rare cases, doulas have been asked to leave the labor room (Eftekhary et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been suggested that collaborative care by doulas positively impacts the mother's perception of her birth, interprofessional tension can result in a negative experience (Gilliland, 2002;Papagni & Buckner, 2006). In fact, it is not unusual to fi nd confl ict between maternity care providers and Doulas have been in the process of integrating into the maternity care system for the last 30 years.…”
mentioning
confidence: 99%
“…The positive Modern hospital maternity care practices have reduced the availability of an attending nurse to remain with a mother during labor. A result of this has been the loss of having someone at the bedside to offer continuous support throughout the birthing process (Papagni & Buckner, 2006). One study found that new mothers expected their nurse to spend 53% of her time offering support, but only 6%-10% of the nurse's time was actually engaged in labor support activities (Tumblin & Simkin, 2001).…”
mentioning
confidence: 99%
“…Studies examining the impact of continuous support by doulas report significant reductions in cesarean births, instrumental vaginal births, need for oxytocin augmentation, and shortened durations of labor (Campbell, Lake, Falk, & Backstrand, 2006;Klaus & Klaus, 2010;Newton, Chaudhuri, Grossman, & Merewood, 2009;Papagni & Buckner, 2006;Sauls, 2002). Continuous support also has been associated with higher newborn Apgar scores (greater than 7) and overall higher satisfaction by mothers with the birthing process (Sauls, 2002).…”
mentioning
confidence: 99%
“…Por un lado crea vida, constituyendo para algunas lo mejor que pudo pasar tras el embarazo (1), pero a la vez puede ser el evento más doloroso que experimenta, implicando una experiencia psicosocial profunda, que pone a prueba su feminidad y competencias personales (2,3), limitando sus habilidades funcionales, principalmente en la disminución del control que ella puede mantener frente a su propia fisiología (3). Por este hecho, la idea de que la mujer necesita ser acompañada durante este proceso no es nueva, incluso antes de que se instaurara la matronería y enfermería, era habitual encontrar a mujeres que se dedicaban a acompañar a otras durante este proceso (4).…”
Section: Introductionunclassified